Effects of evaporative conditions on the performance of recovered residue of modified emulsified asphalt - Huang, Haibing; Xu, Zujie; Zeng, Enjiu; Liu, Bin; Xu, Wen (Frontiers in Built Environment, 2024)
Emulsified asphalt has become a popular green material in modern road construction due to its environmentally friendly and energy-saving characteristics. The method of obtaining residues is crucial for accurately evaluating the performance of emulsified asphalt and ensuring the quality of road construction. The evaporated residues of 3% and 6% SBR modified emulsified asphalt and 6% SBS modified emulsified asphalt were obtained by the low-temperature evaporation (LTE) method and the direct heating (DH) method, respectively. The rheological properties of the modified asphalt residues were tested by the temperature frequency sweeping (TFS), multi-stress creep recovery (MSCR), and linear amplitude sweeping (LAS) tests using the dynamic shear rheometer (DSR), and their aging resistance in the form of carbonyl index was measured by the Fourier infrared spectroscopy (FTIR). The test results showed that, as compared to the DH method, the SBR modified emulsified asphalt residue obtained by the LTE method had higher elastic recovery rate, lower irrecoverable creep compliance, smaller accumulated performance deformation, longer fatigue life, and higher aging resistance, indicating that the LTE method using the low-temperature curing conditions (25 °C, 24 h -60 °C, 24 h) is more suitable for curing the SBR modified emulsified asphalt. However, the opposite trends of the performance indices except the aging resistance were observed for the SBS modified emulsified asphalt residue obtained from the LTE method, showing that the high-temperature curing condition (120 °C, 30 min -163 °C, 1 min) can give the SBS modified asphalt residue better rheological properties and higher fatigue resistance performance, but it also has the disadvantage of weakening the aging resistance. Therefore, in practical application, an appropriate curing temperature should be selected to condition the SBS modified emulsified asphalt for balancing its rheological performance and aging resistance.